Release Kinetic Studies of Aspirin Microcapsules from Ethyl Cellulose, Cellulose Acetate Phthalate and their Mixtures by Emulsion Solvent Evaporation Method - Dash, Vikas (Österreichische Apotheker-Verlagsgesellschaft, 2010)
The present study was oriented towards microencapsulation of aspirin and the study of its release kinetics. The desired encapsulation was achieved by emulsion solvent evaporation method using ethyl cellulose (EC), cellulose acetate phthalate (CAP) and their mixture (1:1) of polymeric constituents. Characterization of the formulations was performed by size, shape, drug loading efficiency and in-vitro drug release analysis. The in-vitro release profiles from different polymeric microcapsules were applied on different kinetic models. The prepared microcapsules were found free flowing and almost spherical in shape with particle sizes ranging from 300–700μm, having a loading efficiency of 75–85%. The best fit model with the highest correlation coefficient was observed in Higuchi model, indicating diffusion controlled principle. The n value obtained from Korsemeyer-Peppas model varied between 0.5–0.7, confirming that the mechanism of drug release was diffusion controlled. Comparative studies revealed that the release of aspirin from EC microcapsules was slower as compared to that of CAP and their binary mixture.